2021
DOI: 10.3389/fonc.2020.598464
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of circRNAs in Liver Cancer Immunity

Abstract: Circular RNAs (circRNAs) are stable covalently closed non-coding RNAs (ncRNAs). Many studies indicate that circRNAs are involved in the pathological and physiological processes of liver cancer. However, the functions of circRNAs in liver cancer immunity are less known. In this review, we summarized the functions of circRNAs in liver cancer, including proliferative, metastasis and apoptosis, liver cancer stemness, cell cycle, immune evasion, glycolysis, angiogenesis, drug resistance/sensitizer, and senescence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 187 publications
0
16
0
1
Order By: Relevance
“…Indeed, circRNAs are dysregulated in numerous human diseases including cancer, and there are recent studies describing the upregulation or downregulation of various circRNAs in several tumors [194] . For instance, circRNAs hsa-circ-002059 and circFAM169A are downregulated in gastric cancer and bladder cancer, respectively [199,200] . On the contrary, circPTK2 and circTCF25 are upregulated in bladder cancer [199] .…”
Section: Circular Rnas In Hbmentioning
confidence: 99%
“…Indeed, circRNAs are dysregulated in numerous human diseases including cancer, and there are recent studies describing the upregulation or downregulation of various circRNAs in several tumors [194] . For instance, circRNAs hsa-circ-002059 and circFAM169A are downregulated in gastric cancer and bladder cancer, respectively [199,200] . On the contrary, circPTK2 and circTCF25 are upregulated in bladder cancer [199] .…”
Section: Circular Rnas In Hbmentioning
confidence: 99%
“…Due to the closed loop structure, circRNAs are not easily affected by the RNA exonuclease and have the high stability in the human body ( Cao et al, 2021 ). CircRNAs have been observed in various cancers and can affect the occurrence and progression of different cancers, such as colorectal cancer ( Chen J. et al, 2020 ), gastric cancer ( Chen H. et al, 2020 ), and liver cancer ( Tang et al, 2020 ). Evidence has shown that circRNAs could indirectly regulate protein-coding genes through reducing the expression level of related miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic and epigenetic factors are the main ones [38,39]. Multiple recent studies have confirmed that circRNAs play a substantial role in the initiation and progression of various cancers, such as hepatic and renal carcinoma, and bladder, prostate, esophageal, breast, gastric and lung cancer [40][41][42][43][44][45]. Considerable evidence shows that these circRNAs function in a great number of cancers and play essential roles in their occurrence and development [46].…”
Section: Circrnas In Cancermentioning
confidence: 99%